A model for contextual data sharing in smartphone applications. Issue 3 (5th September 2016) - Pandit, Harshvardhan Jitendra; O'Riordan, Adrian
Abstract : Purpose: The purpose of this paper is to introduce a model for identifying, storing and sharing contextual information across smartphone apps that uses the native device services. The authors present the idea of using user input and interaction within an app as contextual information, and how each app can identify and store contextual information. Design/methodology/approach: Contexts are modeled as hierarchical objects that can be stored and shared by applications using native mechanisms. A proof-of-concept implementation of the model for the Android platform demonstrates contexts modelled as hierarchical objects stored and shared by applications using native mechanisms. Findings: The model was found to be practically viable by implemented sample apps that share context and through a performance analysis of the system. Practical implications: The contextual data-sharing model enables the creation of smart apps and services without being tied to any vendor's cloud services. Originality/value: This paper introduces a new approach for sharing context in smartphone applications that does not require cloud services.